PERAN TOKOH AGAMA DALAM MEMUTUS RANTAI PANDEMI COVID-19 DI MEDIA ONLINE INDONESIA - Nurul Aula, Siti Khodijah (Living Islam: Journal of Islamic Discourses, 2020)
Information transmission takes an important role in overcoming the covid-19 pandemic. This role is carried out by various parties, including religious leaders. Religious leaders who have charismatic figures, have a special powers that can influence many actions of the people who become their communities. Messages which delivered by religious leaders have a tendency to be followed both the substance of good and bad messages. Therefore, this study aims to explore the responses of religious leaders in online media. To achieve this goal, this research uses descriptive-analysis method by Anthony Giddens about structuration approach. This paper concludes that a role of religious leaders in dealing with covid-19 plays the role as a shock absorber to other people (motivator), the pandemic information mouthpiece (communicator), and the role model (idol). Their role of religious leaders in preventing covid-19 increasingly strengthens a social hierarchy it has in patron-client relations. This form of relationship makes religious leaders to maximize their potential charismatic leadership. It makes our research further strengthen other research on an influence of religious leaders in the formation of social action.